Online English Learning for Mechanical Engineering Students during the Pandemic: Challenges and Suggestions - Yulima Melsipa Lingga; Karolina (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The COVID-19 pandemic has brought changes to the whole world. This pandemic also has an impact on the learning system in Indonesia. From the previous face-to-face learning to online learning, including for English courses. This study aims to elaborate on what challenges were faced by students during online English learning, and what suggestions were given to face and solve these challenges. The object of this research was the first semester students of Mechanical Engineering at the Tanah Laut State Polytechnic. There were 33 students in the Mechanical Engineering department. By using qualitative research methods from written response data and semi-structured interviews, the results showed that there were challenges in the form of unstable or poor internet connections, sudden power outages, lack of interest in learning, and even running out of internet quota while studying. Students also suggested that each material had a learning video that could be replayed at home. They also suggested giving assignments in the form of direct practice with online interaction so that it was easier to understand and corrected directly by lecturers. Furthermore, they suggested apps for more enjoyable English learning related to a machine or their field. This study provided an overview of the online English learning process for mechanical engineering students during the pandemic. It is hoped that in the future it will be able to come up with better solutions to the existing challenges.